2012
DOI: 10.2355/isijinternational.52.1622
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Trace Amount of Cobalt in a Steel Sample by Two-dimensional On-line Redox Derivatization Liquid Chromatography

Abstract: A two-dimensional on-line redox derivatization HPLC system was developed where ''heart-cutting'' chromatography, in conjunction with on-line redox derivatizaion, was used to isolate specific analytes in complex matrix samples. Cobalt in a stainless steel sample was used as a model analyte to evaluate the performance of the HPLC system developed. We adopted a small column packed with porous graphitic carbon (PGC) treated with hydrogen peroxide as an oxidation derivatization unit and two C18 silica columns which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Hoffmann et al 111 realizaram, através de otimizações instrumentais, determinações na faixa de concentração de ng L −1 para 23 elementos em ligas metálicas. Na mesma linha, LA-ICP-MS foi empregada para determinações de metais em moedas de Ag, 112 ligas de Fe, 113,114 Zn, 115 Mg, 116 Ni 117 e com vários elementos majoritários (Fe, Cu, Ni, Co e Al). 118 Utilizando a otimização de parâmetros como atmosfera gasosa, comprimento de onda do laser no UV, dimensão e número de pulsos para um arranjo de LIBS-LA-ICP-MS, limites de detecção de 0,2 (Mo), 0,3 (Mn) e 0,1% (Cr e Ni) foram obtidos em ligas de Mg. 119 A grande vantagem desse arranjo é a possibilidade de se realizar simultaneamente um mapeamento qualitativo da composição do material pela técnica de LIBS e também a razão isotópica através de técnica de ICP-MS.…”
Section: Técnicas Hifenadas De Determinaçãounclassified
“…Hoffmann et al 111 realizaram, através de otimizações instrumentais, determinações na faixa de concentração de ng L −1 para 23 elementos em ligas metálicas. Na mesma linha, LA-ICP-MS foi empregada para determinações de metais em moedas de Ag, 112 ligas de Fe, 113,114 Zn, 115 Mg, 116 Ni 117 e com vários elementos majoritários (Fe, Cu, Ni, Co e Al). 118 Utilizando a otimização de parâmetros como atmosfera gasosa, comprimento de onda do laser no UV, dimensão e número de pulsos para um arranjo de LIBS-LA-ICP-MS, limites de detecção de 0,2 (Mo), 0,3 (Mn) e 0,1% (Cr e Ni) foram obtidos em ligas de Mg. 119 A grande vantagem desse arranjo é a possibilidade de se realizar simultaneamente um mapeamento qualitativo da composição do material pela técnica de LIBS e também a razão isotópica através de técnica de ICP-MS.…”
Section: Técnicas Hifenadas De Determinaçãounclassified
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15] We recently presented an on-line derivatization method for enhancement of separation selectivity of HPLC. [16][17][18] The HPLC system we used consisted of two separation columns and one derivatization unit placed between them. The derivatization reaction, which will change the chemical form of an analyte compound, proceeds in the derivatization unit so that the analyte migrates in its original form on the first column, while in its converted form on the second column.…”
Section: Introductionmentioning
confidence: 99%
“…We have found that porous graphitic carbon (PGC) displays catalytic redox activity, which can be modified by treating PGC with a solution of a suitable oxidizing or reducing agent. 16,[18][19][20] We thus adopted a small column packed with PGC particles oxidized by hydrogen peroxide as an oxidation derivatization unit and investigated its redox activity and the efficiency of the system for enhancement of separation selectivity using ethylenediaminetetraacetate (EDTA) complexes of some metal ions as model compounds and two C18 silica columns treated with cetyltrimethylammonium ion as separation columns. 16 Co(II)-EDTA was completely oxidized to Co(III)-EDTA by the PGC column, while the other metal-EDTA complexes were eluted as their original oxidation states throughout the system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation